PROCEDURES OF APPOINTMENT TO THE POSITION OF PEOPLE'S JUDGES UNDER THE INFLUENCE OF COLONIAL LEGAL TAXONOMY IN TURKESTAN (Scientific journal of the Fergana State University, 2024)
In the current period, the formation of a high legal culture is recognized as one of the priority directions in the policy of existing countries, which creates the need for research in the field. Therefore, it is important to deepen the scientific and theoretical knowledge of judicial activity, to study its history.